Factors Influencing American Plastic Surgery Residents Toward an Academic Career - Chetta, Matthew D. (Plast Surg (Oakv), 2018)
BACKGROUND: Plastic surgery residency program directors have an interest in recruiting applicants who show an interest in an academic practice. Medical school achievements (ie, United States Medical Licensing Examination® scores, publications, and Alpha Omega Alpha status) are metrics assessed to grade applicants but may not correlate with ultimately choosing an academic career. OBJECTIVE: This study was designed to investigate factors influencing residents’ choices for or against academic careers. METHODS: A 25-item online questionnaire was designed to measure baseline interest in academic plastic surgery and factors that influence decisions to continue on or abandon that career path. This questionnaire was disseminated to the integrated/combined plastic surgery residents during the 2013 to 2014 academic year. RESULTS: One hundred twenty-five respondents indicated that they were currently interested in pursuing academic practice (n = 78) or had lost interest in academic practice (n = 47). Among all respondents, 92.8% (n = 116) stated they were interested in academic careers at the time of residency application, but one-third (n = 41) subsequently lost interest. Those residents who retained interest in academic careers indicated resident/medical student educational opportunities (57%) and complexity of patients (52%) as reasons. Those who lost interest cited a lack of autonomy (43%), publishing requirements (32%), and income discrepancy (26%) as reasons. DISCUSSION: Many residents report losing interest in academics during residency. Traditional metrics valued in the recruitment process may not serve as positive predictors of an academic career path. CONCLUSION: Reasons why residents lose interest are not easily correctable, but mentorship, adequate career counseling, and research opportunities during training remain factors that can be addressed across all residency programs.